Idea of Individual? An exploration of legitimation in innovation and the effects of innovator profile characteristics - Al-Kalby, Mohammed (2017)
This work is intended to explore and critically evaluate matters concerning individual legitimacy in innovation settings with attention set in particular upon the influence of profile characteristics in the legitimation process. The discussion set forth is meant to provide a broad and generalizable theoretical framework from which other research may take inspiration and continue under more specific industry, company, profile characteristic, geographic/regional, or other constraints. Key arguments found within are founded upon extensive literature review and primary research which delves into the experience of innovators as well as managers (those seeking recognition of legitimacy and those who grant it - respectively) in a variety of industries and firm sizes within the UK, and the discussion contained within attempts to extract key themes from the collective experiences of participants within the larger social context. Findings of this research largely follow and corroborate the conclusions of existing literature with elements of legitimacy-seeking behaviors unrelated to profile characteristics being the primary topic of conversation among subjects. However, respondents also confirm experiences of possible intersectionality in attaining legitimacy, resources, and recognition. Some managers appear to grant the greatest amount of support and legitimacy to those who are most like themselves, and innovators are most aware of prejudice in the situations within which they are a minority. Organizations attempt to prevent discrimination and inequality in use of power by following bureaucratic methods which are aimed at focusing upon the value of an innovation rather than the individual from whom it originated, but these procedures are sometimes circumvented still. In all, this dissertation concludes that profile characteristics do indeed appear to play some part in the legitimation process, most notably when innovators are placed also in entrepreneurial roles. This is especially important to managers, investors, and the greater economy in that innovation has been repeatedly linked to economic growth - meaning that placing inequitable barriers may quantifiably disadvantage a firm, industry, or country.